2021
DOI: 10.1021/acsabm.0c01358
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and a Roadmap to Aptamer-Based Sensors for Bloodstream Infections

Abstract: The present review is intended to describe bloodstream infections (BSIs), the major pathogens responsible for BSIs, conventional tests and their limitations, commercially available methods used, and the aptamer and nanomaterials-based approaches developed so far for the detection of BSIs. The advantages associated with aptamers and the aptamer-based sensors, the comparison between the aptamers and the antibodies, and the various types of aptasensors developed so far for the detection of bloodstream infections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 233 publications
(252 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, electrochemical sensors can often be integrated with a smartphone to allow simple signal processing and readouts using an associated app [78] . Given these advantages, many aptamer‐based electrochemical sensors have been developed for the detection of diverse human diseases [16,102–105] …”
Section: Detection Of Sars‐cov‐2 With Aptamersmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, electrochemical sensors can often be integrated with a smartphone to allow simple signal processing and readouts using an associated app [78] . Given these advantages, many aptamer‐based electrochemical sensors have been developed for the detection of diverse human diseases [16,102–105] …”
Section: Detection Of Sars‐cov‐2 With Aptamersmentioning
confidence: 99%
“…[78] Given these advantages, many aptamer-based electrochemical sensors have been developed for the detection of diverse human diseases. [16,[102][103][104][105] There are several recent examples of aptamer-based electrochemical sensors for SARS-CoV-2. For example, Idili et al developed an electrochemical sensor by simply immobilizing an S protein-specific DNA aptamer on electrodes for quantitative detection of SARS-CoV-2 (Figure 7).…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…Culture methods are generally very sensitive and can detect anywhere from 2000 CFU mL −1 down to 1-10 CFU mL −1 but, usually yield results after a few days. [18,19]…”
Section: Culture Of Bacterial Samplesmentioning
confidence: 99%
“…[56] Aside from antibodies, the use of DNA aptamers specific to the target bacteria have been shown to provide the best sensitivity for impedimetric detection platforms. [19] To illustrate this, a nanoporous gold (NPG) surface was functionalized with a thiolated version of the S. Typhi specific DNA aptamer, 5"-SH-TAT GGC GGC GTC ACC CGA CGGGGA CTT GAC ATT ATG ACA-G-3" for the detection of S. Typhi. [57] EIS was carried out after 40 min incubation of bacteria; it was found that there was a rise in the charge transfer resistance, as the bacterial concentration was increased owing to the bacterial accumulation at the redox probe-electrode interface.…”
Section: Impedance-based Biosensorsmentioning
confidence: 99%
“…Fig 5. Comparison of the sequences and secondary structures (a) CD63 aptamer previously reported by Q. Zhou et al19) , and (b) one of the aptamer candidates obtained by single cycle MEFAS.…”
mentioning
confidence: 91%